Issue Cover (December 2015). (December 2015) - Unknown
Abstract : Cover legend: 3D physical model of a clathrin‐coated vesicle. Forty years ago, Barbara Pearse purified clathrin‐coated vesicles for the first time and discovered clathrin. See Robinson, Traffic 2015; 16(12):1210–1238. Read the full article on doi:10.1111/tra.12335